FORCAsT‐gs: Importance of Stomatal Conductance Parameterization to Estimated Ozone Deposition Velocity. (2nd September 2021) - Otu‐Larbi, Frederick; Conte, Adriano; Fares, Silvano; Wild, Oliver; Ashworth, Kirsti
Abstract: The role of stomata in regulating photosynthesis and transpiration, and hence governing global biogeochemical cycles and climate, is well‐known. Less well‐understood, however, is the importance of stomatal control to the exchange of other trace gases between terrestrial vegetation and the atmosphere. Yet these gases determine atmospheric composition, and hence air quality and climate, on scales ranging from local to global, and seconds to decades. Vegetation is a major sink for ground‐level ozone via the process of dry deposition and the primary source of many biogenic volatile organic compounds (BVOCs). The rate of dry deposition is largely controlled by the rate of diffusion of a gas through the stomata, and this also governs the emission rate of some key BVOCs. It is critical therefore that canopy‐atmosphere exchange models capture the physiological processes controlling stomatal conductance and the transfer of trace gases other than carbon dioxide and water vapor. We incorporate three of the most widely used coupled stomatal conductance‐photosynthesis models into the one‐dimensional multi‐layer FORest Canopy‐Atmosphere Transfer (FORCAsT1.0) model to assess the importance of choice of parameterization on simulated ozone deposition rates. Modeled GPP and stomatal conductance across a broad range of ecosystems differ by up to a factor of two between the best and worst performing model configurations. This leads to divergences in seasonal and diel profiles of ozone deposition velocity of up to 30% and deposition rate of up to 13%, demonstrating that the choice of stomatal conductance parameterization is critical in accurate quantification of ozone deposition. Plain Language Summary: Plants open and close their stomata to regulate the uptake of carbon dioxide (photosynthesis) and the release of water vapor into the atmosphere. Trace gases like ozone can also enter the stomata causing damage to leaves, reducing plant growth and productivity in the process. Stomatal conductance, the measure of stomatal opening, is therefore important for assessing the concentration of ozone in the atmosphere and the impacts of pollutants on plants. It is critical that canopy‐atmosphere exchange models capture the processes controlling stomatal conductance and the transfer of trace gases other than carbon dioxide and water vapor. We incorporate three widely used coupled stomatal conductance‐photosynthesis models into a 1‐Dimensional multi‐layer model to assess how the choice of model parameters affect the rate at which ozone is deposited onto plant surfaces. We first validate the model using observations from various forests sites and then compare ozone deposition rates between the best and worst performing model at each site. We find that ozone deposition rates can vary by up 13% in response to changes in model parameters, demonstrating that the choice of stomatal conductance parameterization is crucial in understanding ozone deposition, a major process through which ozone is removed from the troposphere. Key Points: Medlyn coupled stomatal conductance‐photosynthesis model best reproduces observed plant productivity (GPP) across various ecosystems Modeled GPP and stomatal conductance across forest ecosystems differ by up to a factor of 3 between different model configurations Ozone deposition rates could vary by ∼13% depending on stomatal conductance model used with implications for estimated tropospheric ozone